Plant-Associated Bacteria - Gnanamanickam, Samuel S. (Springer Netherlands : Imprint: Springer, 2006)
This volume is developed on the broad theme of plant-associated bacteria. It is envisioned as a resource volume for researchers working with beneficial and harmful groups of bacteria associated with crop plants. The book is divided into two parts. Part I (9 chapters) on beneficial bacteria includes chapters on symbiotic nitrogen fixers, diazotrophs, epiphytes, endophytes and rhizosphere bacteria and deleterious rhizobacteria. Part II (8 chapters) consists of detailed descriptions of 8 genera of plant pathogenic bacteria: Agrobacterium, Clavibacter, soft-rot Erwinia, Pseudomonas, Xanthomonas, Ralstonia, Burkholderia and Acidovorax & Herbaspirillum. There is an opening chapter on the plant-associated bacteria survey, molecular phylogeny, genomics and recent advances. And each chapter includes terminology/definitions, molecular phylogeny, methods that can be used (both traditional and latest molecular tools) and applications.